Bibliometric analysis of flipped classroom trends in physics education: Insights from the Scopus database - Fauji Agusta; Nurul Iqdami Zuniari; Heru Kuswanto; Predy Siswanto; Nadiatul Husna; Sabar Nurohman (Momentum: Physics Education Journal, 2025)
This study aims to analyze research trends related to flipped classrooms in physics learning from 2019 to 2023 through bibliometric analysis. The research trends consistently show a growing interest in flipped classrooms as a relevant and compelling topic in physics education. Using bibliometric mapping techniques, several distinct clusters were identified, including purple, blue, green, and orange clusters. Key keywords such as flipped classroom, physics, and student emerged as prominent themes. Furthermore, the top five authors and affiliated institutions contributing to this research were identified, with the largest contributions originating from Indonesia. The research was conducted by systematically collecting data from the Scopus database using the keywords "flipped classroom" and "physics" for the selected time frame. Data were analyzed using VOSviewer, focusing on three types of visualizations: network visualization, overlay visualization, and density visualization. Microsoft Excel was used to graph publication trends and document distribution, providing additional insights into the results. The findings of this study highlight the significant potential of flipped classrooms to improve students' understanding of physics learning by employing participatory methodologies and engaging students directly in the learning process.